2021
DOI: 10.3389/fpls.2021.664311
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomics and Proteomics Analyses of Leaves Reveals a Freezing Stress-Responsive Molecular Network in Winter Rapeseed (Brassica rapa L.)

Abstract: Winter rapeseed is susceptible to low temperature during winter in Northwest China, which could lead to a severe reduction of crop production. The freezing temperature could stress the whole plant, especially the leaf, and ultimately harm the survival rate of winter rapeseed. However, the molecular mechanism underlying freezing tolerance is still unclear in winter rapeseed. In this study, a comprehensive investigation of winter rapeseed freezing tolerance was conducted at the levels of transcript, protein, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 66 publications
(82 reference statements)
6
15
0
Order By: Relevance
“…In addition, it has become increasingly evident that ROS scavenging enzymes are indispensable to maintain normal cellular redox homeostasis (Ray et al, 2012). In our previous study, ROS scavenging enzyme activities were obviously increased in NS plants under freezing stress (Wei et al, 2021a). These results are in agreement with findings reported by Zeng et al (2018).…”
Section: The Responses Of Physiological and Morphological Characteris...supporting
confidence: 90%
See 3 more Smart Citations
“…In addition, it has become increasingly evident that ROS scavenging enzymes are indispensable to maintain normal cellular redox homeostasis (Ray et al, 2012). In our previous study, ROS scavenging enzyme activities were obviously increased in NS plants under freezing stress (Wei et al, 2021a). These results are in agreement with findings reported by Zeng et al (2018).…”
Section: The Responses Of Physiological and Morphological Characteris...supporting
confidence: 90%
“…Plant samples, freezing stress treatments and overwintering rate assessment One freezing-resistant winter rapeseed cultivar NTS57 (NS, with a more than 85% overwinter survival rate at −26 °C), widely planted in Northwest China and used in this study, was provided by Gansu Agricultural University (Wei et al, 2021a). Seedlings of the cultivar NTS57 were grown in plastic pots (5 L) filled with soil from 2015 to 2017.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Integrated analysis of transcriptomics and proteomics was applied to various crops, such as soybean ( Valdés-López et al, 2016 ), rice ( Wang et al, 2017 ; Anupama et al, 2019 ), maize ( Zhang et al, 2019 ), barley ( Lai et al, 2020 ), and rapeseed ( Mehmood et al, 2021 ; Wei et al, 2021 ). Valdés-López et al (2016) found 10 gene regulatory key modules and a variety of proteins that played roles in the heat tolerance of soybean at high temperatures ( Valdés-López et al, 2016 ).…”
Section: Application Of Multi-omics Approaches In Crop Study At Abiot...mentioning
confidence: 99%